Efek Ekstrak Etanolik Daun Kemuning(Murraya Paniculata Jack.) Terhadap Kolesterol DaraTikus Putih Jantan Diet Tinggi Lemak DanHistopatologi Hepar, Jantung Dan Aortah - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
ABSTRACT This study explored the hypocholesterolemia of ethanolic compound of kemuning leaves and activityf& eliminated coronary heart diseases. High lipid diet rats were given ethanolic compound of kemuning leaves in doses 315 mg/kg body weight (BW) for 90 consecutive days. Blood cholesterol level of rats was determined in 15, 45 and 90 days, and at the end of study, the liver, heart and aorta of rats were done by hystophatological determination to see the lipid accumulation in organs. There were an hypocholesterolemia activity of ethanolic compound of kemuning leaves in 15